2019
DOI: 10.1021/acsearthspacechem.9b00166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acidic Conditions on Surface Properties and Metal Binding Capacity of Clay Minerals

Abstract: Clays are one of the most abundant minerals on the Earth's surface, and they play a significant role in global trace element cycling because of their ability to adsorb and incorporate a range of metal cations. However, to what extent clay surface reactivities are affected by changes in pH of the surrounding environment remains poorly understood. To address this uncertainty, we investigated three common clay minerals (kaolinite, illite, and montmorillonite) and compared their surface properties and metal bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…This link is well developed in modern settings, with extensive kaolinite formation in soils developed on organic and pyrite-rich lithologies such as black shales 22,23 . Despite still constituting an important part of the clay fraction, clay minerals more characteristic of moderate terrestrial weathering conditions (e.g., smectites) are more rapidly dissolved in acidic environments 21,[24][25][26] .…”
mentioning
confidence: 99%
“…This link is well developed in modern settings, with extensive kaolinite formation in soils developed on organic and pyrite-rich lithologies such as black shales 22,23 . Despite still constituting an important part of the clay fraction, clay minerals more characteristic of moderate terrestrial weathering conditions (e.g., smectites) are more rapidly dissolved in acidic environments 21,[24][25][26] .…”
mentioning
confidence: 99%
“…For instance, Hao, Pudasainee, et al. (2019) showed significant increases in the surface areas of clay minerals (kaolinite, illite, and montmorillonite) after exposure to acidic solutions (pH ∼ 0–4), as well as decreased cadmium (Cd) adsorption. Similarly, Jeon and Nam (2019) showed that acidic treatment can decrease the surface functional group density and the proton binding constants of montmorillonite.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals that are released into the environment are a major public health concern due to their toxic nature and persistence, and lead (Pb) is among the most common. A wide range of remediation methods have been investigated to remove heavy metals from water and wastewater, including surface precipitation, ion exchange, electrochemical processes, adsorption, , and a combination of these methods . Of the methods described above, adsorption is considered to be an efficient and economic method of metal remediation, and zeolites are some of the most widely used and low-cost adsorbents .…”
Section: Introductionmentioning
confidence: 99%